Work and retirement plans among older Americans - Katharine G. Abraham; Susan N. Houseman (W.E. Upjohn Institute for Employment Research, 2004)
We compare older workers' plans for work and retirement with their subsequent work and retirement outcomes using panel data from the Health and Retirement Study. Among those with retirement plans, about half indicate they would like to cut back on their work hours or otherwise change the type of work they do prior to, or instead of, fully retiring. Yet, the fraction that follows through on these alternative plans is dramatically lower than the fraction that realizes plans to stop working. Our analysis shows that individuals who likely would need to change jobs in order to reduce their work hours are much less likely to have plans to reduce hours and, conditional on having such plans, are much less likely to follow through on them. Instead, a large fraction of these individuals stop working entirely. Our findings suggest that older workers may face substantial barriers to job change, and we conclude with a discussion of potential policy implications.
Keywords: J26; J22; 330; Ältere Arbeitskräfte; Altersgrenze; Erwerbstätigkeit; Panel; USA